THE NEXUS OF TRADE LIBERALIZATION AND UNEMPLOYMENT IN THE CONTEXT OF AFGHANISTAN - Naderi, Abdul Wahid; Nikzad, Ata Mohammad; Thippeswamy, Eralappa; Nayak, Jayavantha (American Finance & Banking Review, 2022)
Despite this, there have been conducted outnumber of studies on the relationship between trade and unemployment around the world. The purpose of this study is to investigate the nexus between trade and unemployment, and whether trade creates or destroys jobs in the context of Afghanistan. To answer this question, the data was gathered from various sources including the World Bank, and the National Statistics and Information Authority of Afghanistan, from 1990 to 2018. Using ADF (Augmented Dicky Fuller) stationarity test, ARDL Bound test, and causality test. The empirical evidence showed only short-run consequences in one variable which is Gross Domestic Products Per Capita. Further, the study employed diagnostic and stability tests to understand the fitness of the model. Hence, this study surely answers the questions and shows that there is no link between trade and unemployment. Finally, the study evinced only the influence of GDP Per Capita on unemployment. Besides, there is a unilateral causality running from GDP Per Capita toward Unemployment and also the study analyzed that GDP Per Capita has a negative and significant impact on Unemployment in the short run. Eventually, the study suggests that the government needs to reform policy in regard to tackling unemployment through domestic investment. JEL Classification Codes: E24, F1.